Penanaman Pendidikan Karakter Demokratis Dan Toleransi Siswa Melalui Program Bina Kelas(Studi Kasus Di Smk Negeri 8 Surakarta Tahun Pelajaran 2015/2016) - Pratama, Helmy (2016)
This study aims to describe the planting, constraints and solutions in inculcation education democratic character and tolerance students through community development program class at SMK Negeri 8. The research data gathered through informants, places and events, as well as documents. Engineering data collection using the method of observation, interview, documentation. The analysis of the data to use the interactive model that has several stages, namely data collection, data presentation, data reduction and withdrawal of the conclusion. Planting a democratic character education and tolerance through community development program class at SMK Negeri Surakarta, 8 students have the attitude of selfless, courageous stated opinions, free to participate in school activities, students do not distinguish between men and women, approved the results of the decisions together, mutual trust between friends, have a sense of community, accept the shortcomings of others, can cooperate with friends of different backgrounds , open and accept other people's opinions. Constraints in the cultivation of the democratic character of education and tolerance through community development program class at SMK Negeri Surakarta 8, students who are less confident, the existence of a dispute between friends, selfish attitudes of students who are still high, and is not concerned with the shortcomings of others, lack of awareness in terms of the attitude of forgiving, still covered. A solution to the constraints of democratic character education and cultivation of tolerance through community development program class at SMK Negeri 8 Surakarta, among them: the affirmation regarding mutual appreciate, providing a motivation so that students more active, providing the motivation to be able to accept the shortcomings of others, do consultations with students who feel inadequate with his friend, the granting of assertiveness through regulations so that those who violated will get sanctions.